Existence of low level westerly Jet Stream over peninsular India during July - JOSEPH, P. V.; RAMAN, P. L. (MAUSAM, 1966)
From an analysis of July rawin and pilot data over peninsular India it is shown that a low level jet stream (as defined by Reiter) exists over peninsular India on a large on a large number of days, with level of wind speed maximum near 1.5 km asl and with core speeds ranging from 40 to 60 kts. High vertical wind shear is observed below the jet core.